Demystifying the impact of customer participation on citizenship behaviors through interpersonal attraction and its contingencies - Chan, Wa Kimmy; Gong, Taeshik; Sharma, Piyush; Chu, Candace (Elsevier, 2022)
This paper addresses the lack of clarity on the linkage between customer participation (CP) and customer citizenship behavior (CCB) by using reinforcement theory to investigate the mediating role of interpersonal attraction (IPA) and the moderating effect of three types of reinforcers (people, task, and environment) in the impact of CP on CCB. Dyadic data from a field survey of both customers and designers from an interior design institute confirms the mediating role of IPA, particularly under high level of shared similarity between customers and employees, and when the task outcomes are better than expected. Moreover, the effect of IPA on CCB is stronger when customers perceive the organizational climate as highly customer-oriented. Besides extending the CP and CCB literature by exploring the impact of IPA on CCB with CP as a mediator and several reinforcers as moderator, this paper also suggests how service firms may influence their customers’ citizenship behaviors.